The link between anger and admiration toward governmental actions and self-reported preventive behaviour in the context of the COVID-19 pandemic - Rupar, Mirjana; Bobowik, Magdalena; Sekerdej, Maciej; Pastor, Elia Soler; Kołeczek, Maryna; Jamróz-Dolińska, Katarzyna; Ghorbani, Foroogh; Mari, Silvia (International journal of psychology, 2024)
In the context of the COVID-19 pandemic, across six correlational studies in four different countries (total N = 4937), we examined the link between citizens' anger with and admiration for the government's actions and decisions (i.e., system-based anger and admiration) and engagement in preventive behaviour. The internal meta-analyses showed that individuals who admired the government's actions were more likely to adopt personal hygiene and social distancing behaviour. Yet, the link between emotions and preventive behaviour differed concerning the target of emotions, especially for anger. Specifically, anger about restrictions imposed by the government was negatively related to preventive behaviours, but this relationship was not significant when the target of anger was the government's overall handling of the pandemic. Our findings emphasise the importance of citizens' emotions and the targets of those emotions during the crisis.
Keywords: pandemie; lidé; Government; zpráva o sobě; Self Report; vláda; Anger; Pandemics; COVID-19; zlost; Humans